Comparison of pull-off, push-out and splitting prism tests for assessment of bonding between fiber-reinforced self-compacting concrete as a repair layer and concrete substrate. - Ali Sademomtazi (Iranian Society of Structrual Engineering (ISSE), 2019)
Considering using self-compacting concrete – because of no need to vibration and flow ability of this kind of concrete under its weight – under challenging situation for consolidation, it would be a very suitable option for using as repair layer in repairing and retrofitting of concrete structures. In this issue, quality of bonding between the repair layer and concrete substrate is one of the most important factors in durability and suitable performance of repairing works. On this base, in this research, some effective factors on bonding between two layers i.e. volume paste, water to cementitious materials and fiber dosages and their effects on rheological properties of repair self-compacting concrete firstly, on mechanical properties of it including compressive strength, tensile strength, modulus of elasticity and shrinkage secondly and on bonding quality between the self-compacting repair layer and concrete substrate finally have been assessed. For assessment of bonding between two concrete layers, three methods including pull-off, push-out and splitting prism have been used. The results show that because of highly effects of shrinkage on bonding, the factors that reduce shrinkage, i.e. volume paste, water to cementitious materials and fiber dosages will increase the bonding of the two concrete layers. In this issue, the exact effect of each of these parameters on bonding between the two concrete layers and the optimum value of them have been assessed. Also, the correlation between all three methods of assessment of bonding between self-compacting concrete as a repair layer and concrete substrate and preciseness of the methods have been found.